Correlation between Forearm Bone Mineral Density Measured by Dual Energy X-ray Absorptiometry and Hounsfield Units Value Measured by CT in Lumbar Spine - Pu, Hong Yu; Chen, Qian; Huang, Kun; Wei, Peng (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
Background Our aim was to determine if the dual-energy X-ray absorptiometry (DXA)-measured forearm bone mineral density (BMD) correlates with the Hounsfield unit (HU) values obtained from computed tomography (CT).Methods A retrospective analysis of 164 patients with degenerative diseases of the lumbar spine was performed. DXA was used to measure the BMD and T-scores of each patient’s forearm. Lumbar CT was used to measure the CT HU values in three axial images of the L1–L4 vertebral bodies, and the average was calculated. According to the preoperative DXA T-score, they were divided into a normal group, an osteopenia group, and an osteoporosis group. Pearson’s correlation coefficient was used to analyze the correlations of CT HU values in L1–L4 with BMD and T-scores in the corresponding vertebral body. The receiver operating characteristic curve (ROC) was used to determine the CT HU thresholds between osteoporosis and non-osteoporosis groups.Results Forearm BMD was moderately correlated with L1–L4 CT HU values (0.4 < R2 < 0.6), and the correlation coefficients (R2) were 0.552, 0.578, 0.582, and 0.577, respectively (all p < 0.001). Forearm T-scores were moderately correlated with L1–L4 CT HU values (0.4 < R2 < 0.6), and the correlation coefficients (R2) were 0.595, 0.609, 0.605, and 0.605, respectively (all p < 0.001). The thresholds of L1–L4 between the osteoporosis group (t ≤ -2.5) and the non-osteoporosis group (t > −2.5) were 110.0 HU (sensitivity 74% and specificity 76%), 112.5 HU (sensitivity 67% and 83% specificity), 92.4 HU (81% sensitivity and 70% specificity), and 98.7 HU (74% sensitivity and 78% specificity), respectively.Conclusions Based on the moderate positive correlation between forearm DXA-measured BMD and HU values, forearm DXA provides a theoretical basis for evaluating lumbar vertebral bone mass. Preoperative forearm DXA may be useful in the formulation of surgical plans and the prevention of postoperative complications in patients with lumbar degenerative diseases.
Keywords: osteoporosis; CT Hounsfield unit value ·; dual-energy X-ray absorptiometry; forearm; lumbar degenerative disease